Incidence and Severity of Crown Gall Disease of Cherry, Apple and Apricot Plants Caused by Agrobacterium tumefaciens in Nagar Valley of Gilgit-Baltistan, Pakistan - Ali, Hussain; Ahmed, Khalil; Hussain, Azhar; Imran (Pakistan Journal of Nutrition, 2010)
The crown gall is a world wide tumor forming disease of the plants and are a major problem for plant nursery industries. This disease is caused by pathogenic species of soil borne bacteria Agrobacterium and cause great economic loss in fruit plants. From July to November in 2008 an extensive survey was conducted in five villages (Chalt, Skindarabad, Gulmit, Askurdas and Nagarkhas) of the Nagar valley of Gilgit-Baltistan randomly by walking in a zigzag pattern and examined the plants for typical curly top symptoms to determine the incidence and severity of crown gall on cherry, apple and apricot plants. A total of 6100 cherry, 6900 apple and 8000 apricot plants were inspected and the mean incidence of crown gall on cherry plants was found to be 5360 (87.87%), apple plants 6069 (87.96%) and in apricot plants 00 (00.00%). In cherry plants, the severity of the disease observed varied from 33.80-40% in mild, 20-34.49% in moderate and 27.85-40% in severe. While in the apple plants it varied from 36.81-42.5% in mild, 29.14-34.49% in moderate and 27-30.31% in severity. There was no infestation of crown gall in apricot plants. A total of 35 samples (15 soil samples; 1 from each orchard of each village and 20 tumor samples; 2 from each orchard of cherry and apple infected plants) from each inspected village were cultured on modified selective medium (3-Ketolactose agar). The growth of Agrobacterium tumefaciens was identified on the basis of colony characteristics and biochemical tests based on Bergey’s Manual of determinative Bacteriology. A 100% infestation of A. tumefaciens was observed from both the plant and soil samples except for the soil sample cultures from the apricot orchard. All the 30 A. tumefaciens strains isolated from the soil specimens and infected cherry and apple plant tumors were tested against six different antibiotics by disc diffusion method. All the strains were resistant against Lincomycin, Amoxycillin, Ampincillin and Cloxacillin while Cephradine, Tetracycline and Dioxycycline, showed intermediate sensitivity.